TAS’IR (PRICE FIXING) DALAM PERSPEKTIF MAQASHID AL-SYARI’AH - Didin Baharuddin (IAIN Ambon, 2017)
The condition of the price of goods on the market has ups and downs. Under normal conditions the Government does not need to intervene in the market price of the Islamic economy known as tas'ir. This was done by the Messenger of Allah. However, the Prophet's stance does not apply in critical condition, especially when there is an increase in the price of goods that soar (distortion) caused by ihtikar, tadlis, taghrir, and monopoly. So according to the scholars, tas'ir allowed to realize the benefit for the community in accordance with maqasid al-syari'ah, especially maintaining property (hifz al-mal).